ANALISIS MOBILITAS INTERNAL KARYAWAN PADA PT KERETA API INDONESIA (PERSERO) DIVRE III PALEMBANG - Oktavia Ramadhani; Sabeli Aliya (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This study aims to analyze the implementation of internal employee mobility as a human resource management strategy at PT Kereta Api Indonesia (Persero) Regional Division III Palembang. Internal mobility refers to the process of shifting employee positions within an organization—encompassing promotions, rotations, and demotions—to support operational effectiveness and employee competency development. A qualitative approach was employed, utilizing observation, documentation, and interviews with relevant units during the internship period. The findings indicate that internal mobility has been implemented systematically based on objective parameters such as work competence, tenure, work experience, job status, and educational background. Between January and April 2026, 162 employees underwent internal mobility; job rotation was the most prevalent form (145 employees), followed by promotion (15 employees) and demotion (2 employees). The high rate of rotation reflects the company's proactive efforts to cultivate a workforce that is flexible and adaptable to the dynamic nature of railway operations. Internal mobility has proven beneficial for the company in meeting operational needs, and for employees by broadening work experience, fostering career development, and enhancing work motivation. Recommendations for the company include optimizing transition programs or providing brief orientation sessions before employees assume new roles to minimize adaptation challenges, as well as strengthening the competency mapping database to enhance the objectivity of future policies.